Metalingüística y purismo en la Chronica Adefonsi Imperatoris. Reflexiones sobre un supuesto arabismo (azecuti) (Minerva, 2019)
There are a number of passages in the Chronica Adefonsi imperatoris which contain reference to azecuti, a term which supposedly refers to certain rearguard of the Arab army. We propose that this word be considered as a technical, semantically imprecise, term of Arab / Latin origin.